Adaptation options to reduce the vulnerability of Mekong water resources, food security and the environment to impacts of development and climate change. Report to AusAID - Mainuddin, M.; Hoanh, Chu Thai; Jirayoot, K.; Halls, A.S.; Kirby, M.; Lacombe, Guillaume; Srinetr, V. (CSIRO. Mekong River Commission. International Water Management Institute., 2010)
The report aims to provide critical input to the Mekong River Commission's (MRC) regional Climate Change and Adaptation Initiative (CCAI) which was launched shortly after the formulation of this project. The CCAI is a collaborative regional initiative designed to address the shared climate change adaptation challenges of LMB countries in response to the potential effects of climate change on the socio-economic characteristics and natural resources of the LMB region. MRC has identified need for a more informed understanding of the potential impacts from climate change. To contribute to this aim, the purpose of this report is: 1. To present the framework of climate change analysis and its application to the Basin Development Plan (BDP) Scenarios; 2. To present the results from the application of the Decision Support Framework (DSF) models of the Mekong River Commission (MRC) in order to analyse the impacts of climate change and selected BDP Scenarios on flow regimes; 3. To present climate change impacts on floods and fisheries in the LMB; 4. To present the impact of climate change on the productivity of major crops grown in the basin and their consequences on the overall food security of the basin considering future population growth. 5. To present the results of applying simple adaptation strategies related to agriculture and food security; and 6. To determine further studies necessary to identify suitable adaptation strategies for dealing with such impacts.